Treatment Dilemmas in a Young Man Presenting with Narcolepsy and Psychotic Symptoms - Victoria Fernandez; Sharon Davies; Nicola Walters (Case Reports in Psychiatry)
Psychotic features can be present in both narcolepsy and psychosis, which can result in challenges in diagnosis and management. The prevalence of both conditions is low and the reports in young people are scarce. Our report illustrates the relevance of a thorough differential diagnosis as well as the need to explore treatment avenues based on the evidence available for both narcolepsy and psychosis symptoms to try and maximise the therapeutic impact.